Ambiguity and public good provision in large societies - Bailey, Ralph W.; Eichberger, Jürgen; Kelsey, David (Discussion paper series, 2004)
In this paper we consider the effect of ambiguity on the private provision of public goods. Equilibrium is shown to exist and be unique. We examine how provision of the public good changes as the size of the population increases. We show that when there is uncertainty there may be less free-riding in large societies.